Self‐assembly of multiscale anisotropic hydrogels through interfacial polyionic complexation. Issue 12 (20th June 2020) - Patel, Akhil; Sant, Vinayak; Velankar, Sachin; Dutta, Mayuri; Balasubramanian, Vibishan; Sane, Piyusha; Agrawal, Vishi; Wilson, Jamir; Rohan, Lisa C.; Sant, Shilpa
Abstract: Polysaccharides are explored for various tissue engineering applications due to their inherent cytocompatibility and ability to form bulk hydrogels. However, bulk hydrogels offer poor control over their microarchitecture and multiscale hierarchy, parameters important to recreate extracellular matrix‐mimetic microenvironment. Here, we developed a versatile platform technology to self‐assemble oppositely charged polysaccharides into multiscale fibrous hydrogels with controlled anisotropic microarchitecture. We employed polyionic complexation through microfluidic flow of positively charged polysaccharide, chitosan, along with one of the three negatively charged polysaccharides: alginate, gellan gum, and kappa carrageenan. These hydrogels were composed of microscale fibers, which in turn were made of submicron fibrils confirming multiscale hierarchy. Fibrous hydrogels showed strong tensile mechanical properties, which were further modulated by encapsulation of shape‐specific antioxidant cerium oxide nanoparticles (CNPs). Specifically, hydrogels with chitosan and gellan gum showed more than eight times higher tensile strength compared to the other two pairs. Incorporation of sphere‐shaped cerium oxide nanoparticles in chitosan and gellan gum further reinforced fibrous hydrogels and increased their tensile strength by 40%. Altogether, our automated hydrogel fabrication platform allows fabrication of bioinspired biomaterials with scope for one‐step encapsulation of small molecules and nanoparticles without chemical modification or use of chemical crosslinkers.